Playing therapy for children with disorders from the autistic spectrum - Balog, Erika (Norma, 2024)
Playing is a physical or mental activity that improves a child’s skills of negotiation, problem solving, manual dexterity, sharing, decision making, and group work. Playing affects all parts, structures and functions of the brain. Children with Autism Spectrum Disorder (ASD) have limitations in adaptive behavior, adaptive response, and social interaction. The aim of this work is to investigate how different applications of playing therapy can help children with autism spectrum disorder. Ability to play is usually significantly impaired in these children. The main hypothesis of this research is that play-based therapy can contribute to the improvement of social skills, communication and the ability to overcome challenges in children on the autistic spectrum. In this research, a descriptive method of literature analysis was used, whereby available research and literature on the topic of play as a therapeutic approach for children with PAS were reviewed and analyzed. Study results have shown that play-based therapy can help children with autism spectrum disorder develop social, communication and coping skills. Also, play-based therapy can help children with learning new concepts and improve their problem-solving skills. Parents and other responsible participants should consider adopting this approach because of its many benefits, including helping children on the autism spectrum develop social, communication, and coping skills that are critical to their survival.